The Effect of Pair Passing And Pass Give And Go Training On Football Passing Accuracy of Club P2D FC Muarangamu Players (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study began with the results of observations that had been conducted at the Muarangamu Village Football Field. It was found that there were still many players who did not have good passing skills; most players passed with the wrong technique. This study aims to determine the Effect of Paired Passing and Pass Give and Go Training. This study was conducted using a quasi-experimental method with a Two-Group Pretest-Posttest Design. The population in this study were 20 P2d FC Muarangamu Football Club Players, while the sampling technique used was Total Sampling, where all populations were sampled. The research design used a Pre-Test and Post-Test. The instrument used was the Passing Accuracy test. Data analysis and testing of research hypotheses used the independent t-test (t-test) analysis technique with a significance level of α = 0.05. The test results show that there is an Influence of Paired Passing Training and Pass Give End Go on Football Passing Accuracy. The hypothesis test shows a value (t count 4.813 > t table 1.860), so that it shows that Ho is rejected and Ha is accepted, which means that there is a significant Influence on Increasing Football Passing Accuracy after being treated with the Paired Passing Training Method and Pass Give End Go.